Policy Communication In The Transfer Of Authority To The Provincial Government In Mapping The Impacts of Coastal Development In Probolinggo City - Sutarjo; Diding Bajuri; Anye Widuri; Nurul Jannah Lailatul Fitria (INJECT (Interdisciplinary Journal of Communication), 2026)
Indonesia is pursuing sustainable development in the fisheries and marine sector because the potential for marine economic growth offers great opportunities for community welfare. The utilization of the marine sector is classified into the utilization of living resources, extraction of non-living resources, commercialization and trade, and responses to marine sustainability challenges. Initially, this authority was regulated by local governments in coordination with provincial governments. As is the case in Probolinggo City, coastal development is the responsibility of the East Java Provincial Government. This is interesting to study, particularly in relation to the implementation of policies after the transfer of authority and the impacts of policy transitions. This study uses a qualitative approach with descriptive analysis. A descriptive qualitative research design was chosen because this study focuses on descriptive elaboration of the research subject. The results show that policy implementation in terms of communication, resources, disposition, and bureaucracy has generally been effective. Furthermore, the policy transition of the East Java Provincial Government's transfer of authority has created impacts. These impacts are both positive and negative. The impacts of policy implementation can be seen in the handling of public issues and the parties involved in policy implementation, the impact on conditions or groups outside the policy's targets and objectives, and the impact on current conditions and future conditions.